(untitled) - Galston, Arthur W. (Englewood Cliffs, N.J., 1980)
Fits short course in plant physiology or functional botany for students of agronomy, horticulture, forestry. 1 sem/2 quarter-Ag students and horticulture. Supplement to plant science, 1st sem. botany, plant physiology.
Keywords: Plant physiology,Sinh lý học thực vật